CMC Determination and Thermodynamic Micellisation Of NPE Surfactant In Aqueous And CH3OH – H2O Solvents (Baghdad Science Journal, 2025)
The critical micelle concentration (CMC) of nonylphenolethoxylate (NPE) surfactant has been determined by measuring the surface tension as a function of the molar concentration of the surfactant in aqueous and binary mixture of water + methanol solutions at a temperature range from 20?C to 35?C. The interfacial parameters ?max, Amin, ?cmc and ?G?ads were calculated. The results indicate that the CMC increases as the temperature increases and that the addition of methanol the CMC decreases. The thermodynamic parameters such as standard Gibbs free energy (?G?), enthalpy (?H?), and entropy (?S?) of micellization were estimated using the change of CMC with temperature. The enthalpy – entropy compensation behavior of the surfactant was evaluated and a good linearity in the compensation plot has been observed.